2020
DOI: 10.1016/j.jadohealth.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Weight Reduction Behaviors Among European Adolescents—Changes From 2001/2002 to 2017/2018

Abstract: The purpose of this study was to analyze changes in the prevalence of weight reduction behaviors (WRBs) among European adolescents from 26 countries between 2001/2002 and 2017/ 2018. The impact of the perception of body weight on WLB was also analyzed, with particular attention being paid to overestimation. Methods: The data of 639,194 European adolescents aged 11, 13, and 15 years who participated in the Health Behaviour in School-aged Children survey were analyzed. Age-standardized prevalence rates of WRB we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…First, all responses in the HBSC study are self-reported, leading to potential recall bias. As regards the differences in self-reported versus the direct height and weight, physical activity measurements noted, self-reported values tend to be typically greater than objectively measured values [ 29 ], while the self-reported weight tends to be lower when measured for girls and higher for boys [ 30 ]. This suggests that the rates provided in this study may not estimate the true magnitude of the level of overweight and obesity together with physical activity, even though the behavioural trends within the Baltic countries are noted and kept throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…First, all responses in the HBSC study are self-reported, leading to potential recall bias. As regards the differences in self-reported versus the direct height and weight, physical activity measurements noted, self-reported values tend to be typically greater than objectively measured values [ 29 ], while the self-reported weight tends to be lower when measured for girls and higher for boys [ 30 ]. This suggests that the rates provided in this study may not estimate the true magnitude of the level of overweight and obesity together with physical activity, even though the behavioural trends within the Baltic countries are noted and kept throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Two other papers in this supplement examine weight reduction and sleep patterns, which are strongly related to mental health and well-being [8,9]. Gariepy et al, using HBSC data across two cohorts (2014, 2018) from 24 countries, examine sleep patterns of adolescents, and the findings confirm the universality of insufficient sleep for adolescents: most adolescents (32%e86%) do not meet sleep recommendations for young people [8].…”
Section: Mental Health and Well-beingmentioning
confidence: 98%
“…Articles in this supplement also examine specific issues related to mental health and well-being such as weight reduction behaviors and sleep patterns. Dzielska et al [9] examine weight reduction behaviors among European adolescents in the 2001e 2002 and 2017e2018 HBSC surveys. Overall, 18.0% of girls and 10.2% of boys reported weight reduction behaviors; however, there was a significant increase in the prevalence of weight reduction behaviors among boys but not girls in most countries [9].…”
Section: Mental Health and Well-beingmentioning
confidence: 99%
“…Dzielska et al [9] examine weight reduction behaviors among European adolescents in the 2001e 2002 and 2017e2018 HBSC surveys. Overall, 18.0% of girls and 10.2% of boys reported weight reduction behaviors; however, there was a significant increase in the prevalence of weight reduction behaviors among boys but not girls in most countries [9]. Gariepy et al [10] examine sleep patterns of adolescents and find insufficient sleep on school days to be a cross-national phenomenon.…”
Section: Mental Health and Well-beingmentioning
confidence: 99%